DIGITAL LITERACY AND ACADEMIC PERFORMANCE OF STUDENTS’ SELF-DIRECTED LEARNING READINESS - Dina Merris Maya Sari (Universitas Negeri Surabaya, 2022)
The students mostly use the internet in communication and academic activities as digital literacy competencies in Industrial Revolution 4.0 era. It is called self-directed learning readiness when the students take the initiative without others’ helping in planning, implementing, and evaluating learning processes. This study aimed to analyze the relationship between digital literacy competence and students’ academic performance in self-directed learning readiness in the English language department in STKIP PGRI Sidoarjo. This study used a quasi-experimental design. The research instrument was a questionnaire and students’ GPA data. The relationship between digital literacy competence and academic performance on self-directed learning readiness was analyzed with a chi-square test. The research variables were measured using an ordinal scale based on the attitudes and statements answered by the students. The data were analyzed using correlation test statistics to test the proposed hypothesis. The analysis of self-directed learning readiness scores showed that 79,2% of students had high levels and 20,8% of students had low levels. Chi-square test results to assess the relationship between digital literacy competence and self-directed learning readiness obtained a p-value of 0.198, and the relationship between academic performance and self-directed learning readiness showed a p-value of 0.493. There was a significant relationship between digital literacy competence and academic performance with self-directed learning readiness in EFL students.